2016
DOI: 10.1007/s00296-016-3588-y
|View full text |Cite
|
Sign up to set email alerts
|

A reliability study using computer-based analysis of finger joint space narrowing in rheumatoid arthritis patients

Abstract: Author identifying informationConflict of Interest: All the authors declare no conflict of interest.Funding: This study has no relevant funding. AbstractObjectives: The joint space difference index (JSDI) is a newly developed radiographic index which can quantitatively assess joint space narrowing progression of rheumatoid arthritis (RA) patients by using an image subtraction method on a computer. The aim of this study was to investigate the reliability of this method by non-experts utilizing RA image evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Furthermore, we found good relationship between the semiautomated method using tomosynthesis images and the semiquantitative scoring method in MCP and PIP joints. Intra-observer agreement of the semi-quantitative scoring method for radiography was moderate to almost perfect with ICC values of 0.589-0.839 in our previous article [28], while intra-observer agreement was almost perfect with the semi-automated method by non-experts in this study. Similarly, inter-observer agreement was poor to fair with the semiquantitative scoring method for radiography and tomosynthesis by experts, while inter-observer agreement was almost perfect with the semi-automated method by nonexperts in this study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, we found good relationship between the semiautomated method using tomosynthesis images and the semiquantitative scoring method in MCP and PIP joints. Intra-observer agreement of the semi-quantitative scoring method for radiography was moderate to almost perfect with ICC values of 0.589-0.839 in our previous article [28], while intra-observer agreement was almost perfect with the semi-automated method by non-experts in this study. Similarly, inter-observer agreement was poor to fair with the semiquantitative scoring method for radiography and tomosynthesis by experts, while inter-observer agreement was almost perfect with the semi-automated method by nonexperts in this study.…”
Section: Discussionsupporting
confidence: 49%
“…Radiography remains the reference modality for the diagnosis and follow-up of patients with RA, which is recommended by American College of Rheumatism and the European League Against Rheumatism [1,27]. However, conventional radiographic scoring methods are subjective and suffer from reader variation [28,29]. Specialized training is also required, which limits the number of qualified readers.…”
Section: Discussionmentioning
confidence: 99%
“…However, intra-and interobserver reliability for the SvdH scoring system on radiograph in 51 RA patients by the same expert (TK) were moderate to almost perfect in a previous study (ICC = 0.589-0.839 and 0.556-0.849, respectively). 20 In conclusion, quantitative PD signal assessment in the subchondral bone region of the MCP joints is a simple technique, which may predict radiographic progression in the hand joint than conventional semi-quantitative scoring, quantitative ROI method or qualitative PD signal assessment in the subchondral bone region in RA patients on…”
Section: Discussionmentioning
confidence: 88%
“…Hatano et al . 28 reported that the inter- and intra-observer reliabilities using the software by non-experts were almost perfect (inter-observer ICC; 0.979 and intra-observer ICC; 0.976, respectively). The results of the reliability in the clinical section of this study were consisted with the previous study.…”
Section: Discussionmentioning
confidence: 99%